2016
DOI: 10.1007/s40256-016-0205-0
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Place of Ezetimibe/Atorvastatin in the Management of Hyperlipidemia

Abstract: Statin-ezetimibe combinations are a potentially advantageous therapeutic option for high-risk patients who need additional lowering of low-density lipoprotein cholesterol (LDL-C). These combinations may overcome some of the limitations of statin monotherapy by blocking both sources of cholesterol. Recently, a fixed-dose combination with atorvastatin, one of the most extensively studied statins, was approved and launched in several countries, including the USA. Depending on atorvastatin dose, this combination p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…However, products of 3-hydroxy-3-methylglutaryl-coenzyme A are also utilized for essential biomaterials, and inappropriate statin prescriptions could result in statin-associated symptoms in the muscles, pancreas, and central nervous system [ 4 , 5 ]. Recently, a combination therapy comprised of statins and ezetimibe has demonstrated the potential to overcome limitations of statin monotherapy via the inhibition of intestinal cholesterol absorption and the increase of cholesterol excretion [ 6 ]. In addition, a PSCK9 inhibitor, a suppresser of hepatic LDLR expression, has also indicated potential in non-statin hypolipidemic therapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, products of 3-hydroxy-3-methylglutaryl-coenzyme A are also utilized for essential biomaterials, and inappropriate statin prescriptions could result in statin-associated symptoms in the muscles, pancreas, and central nervous system [ 4 , 5 ]. Recently, a combination therapy comprised of statins and ezetimibe has demonstrated the potential to overcome limitations of statin monotherapy via the inhibition of intestinal cholesterol absorption and the increase of cholesterol excretion [ 6 ]. In addition, a PSCK9 inhibitor, a suppresser of hepatic LDLR expression, has also indicated potential in non-statin hypolipidemic therapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that there is a large inconsistency in individual response to several different statins and doses. This rather unpredictable response is supposedly due to a complex interaction between genetic and environmental factors [45]. Combination of Ezetimibe-statins provides statistically significant improvements in triglycerides (TG), HDL-C, non-HDL-C, apolipoprotein B (ApoB) and high-sensitivity C-reactive protein (hs-CRP) [46].…”
Section: Intestinal Sterol Absorption Inhibitorsmentioning
confidence: 99%
“…Additional benefits are achieved when ezetimibe is combined with atorvastatin or rosuvastatin [37][38][39][40]. Ezetimibe may also be combined with bile acid sequestrants, resulting in an additional reduction of LDL-C levels [29].…”
Section: ) Patients With Statin-intolerancementioning
confidence: 99%